Effects of brown algal fertilizers on tomato yield and fruit quality - SAID BAROUD; SAIDA TAHROUCH; ABDELHAKIM HATIMI (Asian Journal of Agriculture, 2025)
Abstract. Baroud S, Tahrouch S, Hatimi A. 2025. Effects of brown algal fertilizers on tomato yield and fruit quality. Asian J Agric 9: 454-462. The purpose of this study was to evaluate the biofertilizer potential of three brown algae: Fucus spiralis, Cystoseira gibraltarica, and Bifurcaria bifurcata. Over ninety days, the growth of the algae was monitored. The algae were applied in two different forms and at varying concentrations: aqueous extract (0.5%, 1%, and 2%) and amendment (C1, C2, and C3). For each algal treatment, ten pots were used, with one plant per pot (10 replicates per treatment). Each pot received 50 mL/week of the algal extract, corresponding to three concentrations (0.5%, 1%, and 2%). For the amendment, the treatments consisted of three increasing concentrations: C1 (2.5 g/pot), C2 (5 g/pot), and C3 (10 g/pot). The low concentration algal extracts significantly improved growth parameters—such as length of the aerial part, root length, plant height, fresh weight, and dry weight—and yield indicators like the number of flowers, fruits, and the fresh weight of fruits, compared to the control. Fertilization with F. spiralis amendment C1 notably enhanced the length of the aerial part, root length, and overall plant height (115, 41, and 156 cm, respectively). Improvements in sugar content, Brix, and fruit diameter were observed in fruits treated with C. gibraltarica at 1% (4.95%, 4.33%, and 55.66 mm, respectively). Additionally, the algal extracts with low concentrations of B. bifurcata and F. spiralis exhibited the highest mineral content in tomato leaves. The aqueous extract of B. bifurcata at 0.5% showed the highest levels of organic matter and total nitrogen in leaves (84.68% and 2.1%, respectively). Overall, these three algae proved to be effective and suitable candidates for developing biostimulants aimed at enhancing tomato growth, yield, and fruit quality. This study provides valuable information regarding the identification and application of Moroccan algae resources in agriculture.